Current status of surgical treatment for pediatric drug-resistant epilepsy - ZHANG Xiao-lei; DONG Sheng; GUO Jia-he; GUO Yi; YANG Xue-jun (Chinese Journal of Contemporary Neurology and Neurosurgery)
Pediatric drug-resistant epilepsy (DRE) significantly affects children's neurodevelopment and quality of life, often accompanied by cognitive dysfunction and behavioral abnormalities, imposing a heavy economic and psychological burden on families and society. Surgery is an effective treatment for DRE, especially for children who do not respond to medication. This article reviews the current status of surgical treatment for pediatric DRE, discussing the necessity and timing of surgery, surgical indications, and preoperative evaluation. It introduces the applications of resective and palliative surgeries and explores the development of new technologies such as laser interstitial thermotherapy (LITT) and high - intensity focused ultrasound (HIFU). This review provides a theoretical foundation for the advancement of pediatric epilepsy surgery toward more minimally invasive and precise approaches.